Portrait of the use of carbapenemics in a hospital belonging to the unified health system (Research, Society and Development, 2022)
Antimicrobials are an important therapeutic arsenal against graves, as they have broad-spectrum bactericidal activities and better stability against βlactamases. This group of antimicrobials acts against gram-positive and gram-negative, aerobic and aerobic bacteria, and mainly in nosocomial infections. However, the presence of carbapenemases constitutes one of the main mechanisms of resistance. This article aims to identify the profile of patients who used carbapenem antimicrobials and quantify the consumption of this class based on the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) methodology in a high-complexity hospital in the year 2020. This is an observational and retrospective study in a hospital belonging to the Unified Health System (SUS). Data collection was performed based on medical records, prescriptions, and antimicrobial control forms. A total of 120 patients were included in the study, the mean age was 52 ± 17.58 years, and the mean length of stay in the hospital was 33 ± 29.68 days. Carbapenem requests were analyzed, of which 74% were meropenem, 21% imipenem + cilastatin, and 5% ertapenem. The most consumed carbapenem during the study period was meropenem (DDD 252.87). Our findings made it possible to trace the profile of use of drugs belonging to the class of carbapenems in the high complexity hospital, demonstrating their importance, especially in the treatment of critically ill patients.